2017
DOI: 10.1038/s41598-017-12198-6
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the vaginal microbiota and vaginal immune mediators in women from sub-Saharan Africa

Abstract: In cross-sectional studies increased vaginal bacterial diversity has been associated with vaginal inflammation which can be detrimental for health. We describe longitudinal changes at 5 visits over 8 weeks in vaginal microbiota and immune mediators in African women. Women (N = 40) with a normal Nugent score at all visits had a stable lactobacilli dominated microbiota with prevailing Lactobacillus iners. Presence of prostate-specific antigen (proxy for recent sex) and being amenorrhoeic (due to progestin-inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 57 publications
18
94
0
Order By: Relevance
“…A study by Birse et al, 2017 found no significant association between DMPA and bacterial diversity (Shannon Diversity Index) in non-sex workers, however women with BV were not excluded (43). The results of the present study support those of Jespers et al, 2017 who demonstrated that injectable progestins (including DMPA) were associated with VMB diversity and reduced concentration of lactobacilli in African women (10). Although another study included non-sex workers of varying ethnicities, and included BV, bacterial diversity (by inverse Simpson’s index) was significantly lower in women on OCPs than DMPA or not on hormonal contraceptives, and although not statistically significant, women on DMPA had greater bacterial diversity than women not on hormonal contraceptives (8).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A study by Birse et al, 2017 found no significant association between DMPA and bacterial diversity (Shannon Diversity Index) in non-sex workers, however women with BV were not excluded (43). The results of the present study support those of Jespers et al, 2017 who demonstrated that injectable progestins (including DMPA) were associated with VMB diversity and reduced concentration of lactobacilli in African women (10). Although another study included non-sex workers of varying ethnicities, and included BV, bacterial diversity (by inverse Simpson’s index) was significantly lower in women on OCPs than DMPA or not on hormonal contraceptives, and although not statistically significant, women on DMPA had greater bacterial diversity than women not on hormonal contraceptives (8).…”
Section: Discussionsupporting
confidence: 91%
“…However two independent prospective studies have shown the Shannon Diversity Index remains stable across the menstrual cycle (19, 48). We thus believe results represent an accurate depiction of the effect of MPA on VMB diversity and the vaginal microenvironment in sex workers, especially given results of recent studies (8, 10).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations